Efektivitas Penggunaan Bahasa Indonesia Sederhana dalam Edukasi Kesehatan Masyarakat - Dali, Meilina Widya; Monorfa, Fidyawati; Talani, Juniyati R.; Siallagan, Rahel Mora N.; Sino, Nazifah Rizky; Rauf, Nur Novianita; Naue, Mohamad Dill; Bagoe, Aisyah Amini Cevestia; Djibu, Rizka Cahyani; Hamka, Zahwa; Tina, Dinah Saniyyah Novianti; Minabari, Mohamad Iswan; Setiawati, Ayu; Septia, Anna; Lalunggeli, Iyan; Hamzah, Nurfadillah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The use of simple Indonesian in public health education is an important strategy for improving the effectiveness of health information delivery. This study aims to analyze the implementation of health education in community health centers, the use of simple Indonesian, community response and comprehension levels, and its impact on participation and health behavior. Health education is carried out regularly through various activities with the support of visual and print media. The results of the analysis show that the use of simple, clear, and easy-to-understand language improves community understanding, encourages active participation, and helps the acceptance of messages related to disease prevention and clean and healthy living behaviors. Although there are obstacles in the form of regional language differences, adjustments in the delivery methods by health workers can overcome these obstacles. Thus, the use of simple Indonesian plays an important role in supporting the success of public health education.